Application of a validated ultra performance liquid chromatography–tandem mass spectrometry method for the quantification of darunavir in human plasma for a bioequivalence study in Indian subjects - Gupta, Ajay; Singhal, Puran; Shrivastav, Pranav S.; Sanyal, Mallika (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2011)
A simple, precise and rapid ultra performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) method has been developed and validated for the quantification of darunavir, a protease inhibitor, using darunavir-d9 as internal standard (IS). The method involved liquid–liquid extraction of darunavir and IS in methyl- tert-butyl ether from 50 μL human plasma. The chromatographic separation was achieved on an Acquity UPLC BEH C18 (50 mm × 2.1 mm, 1.7 μm particle size) analytical column under gradient conditions, in a run time of 1.6 min. The precursor → product ion transitions for darunavir ( m/ z 548.1 → 392.0) and IS ( m/ z 557.1 → 401.0) were monitored on a triple quadrupole mass spectrometer, operating in the multiple reaction monitoring (MRM) and positive ion mode. The method was extensively validated for its selectivity, sensitivity, carryover check, linearity, precision and accuracy, reinjection reproducibility, recovery, matrix effect, ion suppression/enhancement, stability and dilution integrity. The linearity of the method was established in the concentration range of 1.0–5000 ng/mL. The mean relative recovery for darunavir (100.8%) and IS (89.8%) from spiked plasma samples was consistent and reproducible. The application of this method for routine measurement of plasma darunavir concentration was demonstrated by a bioequivalence study conducted in 40 healthy Indian subjects for a 600 mg tablet formulation along with 100 mg ritonavir as booster under fast and fed conditions. To demonstrate the reproducibility in the measurement of study data, an incurred sample reanalysis was done with 400 subject samples and the % change in concentration was within ±12%.